SMART GREENHOUSE UNTUK BUDIDAYA TANAMAN HIDROPONIK MENGGUNAKAN ARDUINO BERBASIS TELEGRAM - Hani; Luki hernando (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2023)
Rapid development times on eraglobalisasi currently, has demanded a man to always be inspired and give new ideas in developing appropriate and advanced technology, which can help human beings in ease in carrying out daily activities such as water activity, batam city is one of the industrial cities also have growing land that has been widely used by some people who choose to open businesses in the farming activities in the form of greenhouse, but due to too much a flurry led to a lack of time and lack of cost in hiring another person to replace such activities. so with the existence of these problems made an automatic plant watering tools (smart green house) with the arduino which is already designed back by leveraging application telegram as a means of controlling from a distance, after a testing on prototype watering plants automatically, it can be seen that each of the components used are already working in accordance with the order in which they had already determined by the percentage of success amounting to 90%. and the results obtained at the time when the appliance is turned on the wifi module nodemcu will be directly connected to the wifi signal already inputed into the arduino ide, and soil sensors will detect the status of the land that has been rapid thrusting with the soil sensors and then submit the application to the soil status conditions telegram as an indication to receive the next command.